ANALISIS VEGETASI PENYUSUN HUTAN SAVANA TAMAN WISATA ALAM PULAU MENIPO KABUPATEN KUPANG NTT - Jeriels Matatula; Agustinus Timu Losor; Blasius Paga (Partner, 2022)
Indonesia Biodiversity Wealth is the savanna ecosystem of Menipo Island Nature Tourism Park (TWA). The Savanna type on Menipo Island has similarities with savanna in Africa which includes tropical savanna. The Savanna ecosystem on Menipo Island has an important role in supporting the food needs of herbivorous animals such as deer (Cervus timorensis). Therefore, reduction and decrease in Savanna quality and quantity will reduce herbivore population. Stresses on savanna ecosystems have a major impact on balance and entire ecosystem preservation. There are seven vegetation types that make up savanna on Menipo Island, with three seedling level types, three sapling types, six pole types, and three tree types. The method used is observation, collecting data, and interview. The research result is the vegetation types of vegetation savanna forest in the Menipo island natural tourism park are 7 types with the constituent levels for seedlings consisting of 3 types, 3 types of piles, 6 types of pile levels, and 3 types of tree levels. Key Words:  Method, Seedlings, Savanna, Saplings, Trees, Poles